Lightning the future of education in Brazil: the impact of rural electrification on educational outcomes (2018)
We analyze the impact of rural electricity access on different educational outcomes for children by taking advantage of the priorization criteria of the brazilian program Luz Para Todos (LPT) which determines an assignment variable that extracts the exogenous variation in rural electricity access. Using test scores and census data at the school and child level we establish that having electricity access through LPT has a positive and significant effect on Language and Math test scores for 5th and 9th graders, on literacy likelihood and on approval rates. We argument that the effect is driven by an increase in electricity access and use within schools which empirically remarks the importance of electrical device access and technology use on modern education.